2018
DOI: 10.3390/colloids2030035
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Biosurfactants on Microbial Cell Properties Leading to Hydrocarbon Bioavailability Increase

Abstract: The environment pollution with hydrophobic hydrocarbons is a serious problem that requires development of efficient strategies that would lead to bioremediation of contaminated areas. One of the common methods used for enhancement of biodegradation of pollutants is the addition of biosurfactants. Several mechanisms have been postulated as responsible for hydrocarbons bioavailability enhancement with biosurfactants. They include solubilization and desorption of pollutants as well as modification of bacteria cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(71 citation statements)
references
References 142 publications
(203 reference statements)
3
63
0
5
Order By: Relevance
“…In addition to this distance effect, biofilms could improve assimilation of hydrocarbons through their extracellular matrix. For instance, biosurfactants that have been shown, at least in some cases, to improve the degradation of hydrocarbons could have their efficiency increased in biofilms (Ron and Rosenberg, ; Abbasnezhad et al ., ; Kaczorek et al ., ). The retentive properties of the matrix could enable their accumulation within the matrix where they could reach their critical micellar concentration and thus increase the pseudosolubilization and the mass transfer of hydrocarbons toward the cell.…”
Section: The Eps Matrix As An External Digestion Systemmentioning
confidence: 97%
“…In addition to this distance effect, biofilms could improve assimilation of hydrocarbons through their extracellular matrix. For instance, biosurfactants that have been shown, at least in some cases, to improve the degradation of hydrocarbons could have their efficiency increased in biofilms (Ron and Rosenberg, ; Abbasnezhad et al ., ; Kaczorek et al ., ). The retentive properties of the matrix could enable their accumulation within the matrix where they could reach their critical micellar concentration and thus increase the pseudosolubilization and the mass transfer of hydrocarbons toward the cell.…”
Section: The Eps Matrix As An External Digestion Systemmentioning
confidence: 97%
“…Bioremediation of hydrocarbon contaminated environment, like soil, depends on the bioavailability of the hydrophobic compounds. This could be achieved through different mechanisms which include modification of microbes' cell surface, solubilization, and desorption of the pollutants [117]. A study conducted by Shin et al [118] used a rhamnolipid to remediate phenanthrene contaminated soil by the combined solubilization-biodegradation regime.…”
Section: Bioremediation Of Hydrocarbon Contaminated Soilmentioning
confidence: 99%
“…Biosurfactants have shown to play a huge role in bioremediation of hydrocarbons, metal detoxification and/or removal; and in soil washing technology [112,113,117,119,120,135,147,148,150]. Research conducted by Sachdev et al [158] reported that biosurfactants aid nutrient uptake, including root cell differentiation.…”
Section: Metal Bioremediationmentioning
confidence: 99%
See 1 more Smart Citation
“…When the effectiveness of the biodegradation of hydrophobic impurities is considered, the role of bioavailability in this process is increasingly pointed out [13]. The low solubility of PAHs in water as well as their high sorption to soil particles affect the bioaccumulation of these compounds in the environment.…”
Section: Introductionmentioning
confidence: 99%